Association between schizophrenia and the syntaxin 1A gene - Wong, Albert H. C. (2004)
Both microarray and candidate molecule studies have demonstrated that protein and mRNA expression of syntaxin and other genes involved in synaptic function are altered in the cerebral cortex of patients with schizophrenia.Methods